Primary thymic MALT lymphoma in a patient with Sjögren’s syndrome and multiple lung cysts: a case report - Yusuke Hirokawa; Ryo Fujikawa; Yoshifumi Arai; Yoshiro Otsuki; Toru Nakamura (Surgical Case Reports, 2019)
Abstract Background Thymic mucosa-associated lymphoid tissue (MALT) lymphoma is rare and also known for its association with autoimmune diseases, especially Sjögren’s syndrome (SjS), which could affect the systemic organs, and pulmonary involvement often reveals multiple lung cysts. Case presentation A 40-year-old woman presented with an anterior mediastinal mass and multiple lung cysts on computed tomography. We suspected thymoma concomitant with lymphangioleiomyomatosis and performed a total thymectomy and wedge resection of the lung as a surgical biopsy. The histopathological diagnosis of the mediastinal mass was a MALT lymphoma, and there were no specific findings in the lung specimen. She had a history of SjS, which had been overlooked during the initial work-up. Conclusions A history of SjS should raise suspicion of a MALT lymphoma for the differential diagnosis of an anterior mediastinal mass. A precise history taking is crucial for the correct diagnosis, and we could have avoided a lung resection in our case.